The association between intestinal parasites and anemic syndrome in schoolchildren: A literature systematic review - Garzon-Castaño, Sandra C.; Gil-Grajales, Ángela M.; Echeverri-Herrera, Daniela; Montoya-Giraldo, Luz A.; Uribe-Palacio, Germán D.; López-Muñoz, Diego F.; Giraldo-Ospina, Beatriz (Universidad y Salud, 2023)
Introduction: Intestinal parasitic infections and anemia are a global public health problem. These parasites have a tropism for the small intestine, which affects the micronutrients absorption during erythropoiesis and causes an anemic syndrome due to a low red blood cell count and hemoglobin deficiency. Objective: To establish the association of intestinal parasite infection and anemic syndrome in schoolchildren. Materials and methods: Systematic search of literature published between 2010 and 2021 about the association between intestinal parasitic infections and anemic syndrome in schoolchildren. Results: 1151 publications were identified, which were reduced to 33 when the inclusion and exclusion criteria were applied. There were 9 parasites, and the helminths commonly associated with anemia were A. lumbricoides (27.27%), A. duodenalis y T. trichiura, whereas G. duodenalis (6.06%) was the most frequent protozoan. The regions with most publications were Africa (21), Asia (6), South America (5), and Central America (1). There was a significant association between parasitic infection and anemia (CI=95%). Conclusion: High prevalence of deficiency anemia, such as iron deficiency and megaloblastic anemia, was observed. Also, there was a significant association between a higher percentage of helminth infections and anemic syndrome compared to infections caused by protozoans.